Five cities that could change the future of Antarctica - Salazar, JF; Leane, E; Magee, L; James, P (The Conversation Media Group Ltd, 2016)
Antarctica is at a crossroads. This frozen continent at the bottom of our planet hasthe potential to either become one of the most fiercely contested zones in the world,or the most collaborative.